Integration of Ecotheological and Islamic Economic Values in the Preservation of Local Wisdom of Reog Kendang Towards Global Harmony - Sultoni, Hasan; Santi, Mei (Proceedings of Annual Conference for Muslim Scholars, 2025)
This research addresses the global ecological crisis by proposing a new paradigm that integrates spiritual and social values to ensure cultural and environmental sustainability. The study analyzes the integration of Islamic ecotheological values and Sharia economic principles within the preservation of Reog Kendang, a local tradition in Tulungagung, Indonesia. Adopting a qualitative-interpretive method with an intrinsic case study design, data were collected through participant observation, in-depth interviews, and documentation. Analysis was conducted using the Miles and Huberman model, ensuring a rigorous interpretive depth. The findings reveal that the Reog Kendang community manifests spiritual-ecological values by fulfilling the role of khalifah fil ardh (steward of the earth) through collective prayer, the use of eco-friendly materials, and active nature conservation. Simultaneously, Sharia economic principles are reflected in the ethical management of communal funds, distributive justice, and blessing-based (barakah) social activities. The study concludes that this synthesis creates a model of Islamic ecocultural harmony that preserves indigenous culture, strengthens social solidarity, and supports the Sustainable Development Goals (SDGs). This model serves as a strategic reference for developing a creative economy and cultural preservation framework rooted in Islamic ethical values. This research addresses the global ecological crisis by proposing a new paradigm that integrates spiritual and social values to ensure cultural and environmental sustainability. The study analyzes the integration of Islamic ecotheological values and Sharia economic principles within the preservation of Reog Kendang, a local tradition in Tulungagung, Indonesia. Adopting a qualitative-interpretive method with an intrinsic case study design, data were collected through participant observation, in-depth interviews, and documentation. Analysis was conducted using the Miles and Huberman model, ensuring a rigorous interpretive depth. The findings reveal that the Reog Kendang community manifests spiritual-ecological values by fulfilling the role of khalifah fil ardh (steward of the earth) through collective prayer, the use of eco-friendly materials, and active nature conservation. Simultaneously, Sharia economic principles are reflected in the ethical management of communal funds, distributive justice, and blessing-based (barakah) social activities. The study concludes that this synthesis creates a model of Islamic ecocultural harmony that preserves indigenous culture, strengthens social solidarity, and supports the Sustainable Development Goals (SDGs). This model serves as a strategic reference for developing a creative economy and cultural preservation framework rooted in Islamic ethical values.